Dramaturgy Of Street Performers In Jakarta (A Social Construction Study on The Phenomenon Of Metropolitan Life) - Sukma, Agus Hitopa; Pranawukir, Iswahyu; Misnan, Misnan; Bachtiar, Alfan; Hiswanti, Hiswanti; Alamsyah, Alamsyah (Jurnal Mamangan, 2024)
Life in Jakarta reflects complex social phenomenon, especially related to social inequality striking. This research aims to analyze the dynamics of interaction Street buskers as social "actors" through a dramaturgical approach produce social constructions about the phenomena of metropolitan city life. The methodology used is a qualitative study with in-depth interviews and Participatory observation of four buskers aged 16 to 31 years. The research results show that street buskers apply different strategies on the front stage to build a positive image to attract audience, while backstage, they face challenges emotional and economic intangibles. Social stigma and uncertainty income is the main obstacle in their self-development. this finding emphasizes that interaction with the audience does not only function as a source income but also as a means to build meaning and identity. Thus, this research makes an important contribution to understanding public communication and the role of buskers in the socio-cultural context of Jakarta wider.